An Eyelid Warming Device for the Management of Meibomian Gland Dysfunction - Ngo, William (J Optom, 2019)
PURPOSE: To determine the effectiveness of the MGDRx EyeBag in managing meibomian gland dysfunction. METHODS: This was a prospective, randomized, controlled, observer-masked, bilateral eye study that enrolled 29 participants. Participants were randomized into either the EyeBag group or the control group. The EyeBag group used the EyeBag 10 minutes 2x/day, and the control group remained on their own dry eye treatment regimen (if applicable). All participants were observed at baseline, 2 weeks (2wk) and 4 weeks (4wk). At 4wk, participants in the EyeBag group were asked to stop using the EyeBag. All participants were seen again at 8 weeks (8wk). Primary outcomes were the Ocular Surface Disease Index (OSDI), Current Symptoms Questionnaire (CSQ), meibomian gland score (MG score), and non-invasive tear breakup time (NIBUT). RESULTS: Twenty-five participants completed the study (mean age 38 ± 15 years, 7 male). There was a significant change in OSDI over time for the EyeBag group (mean[lower 95% CI, upper 95% CI], baseline: 39.1[31.1,47.0], 2wk: 26.8[19.7,33.9], 4wk: 26.6[16.5,36.7], 8wk: 27.7[18.4,37.0]; p = 0.01), but not in the control group (p = 0.22), but no significant difference between groups at all time points (all p > 0.27). Symptoms immediately improved after conducting the EyeBag based on at-home CSQ scores (Δ=-5.0 points, p < 0.01), but not in the control group. For both groups, there was no significant change (p-value EyeBag,p-value control) in MG score (0.21,0.17) and NIBUT (0.49,0.06) over time. CONCLUSIONS: The EyeBag may relieve symptoms of dry eye, but the effect on meibomian gland function and tear stability when used for only 4 weeks was undetectable.